Marketing Communication of Entrepreneurs in Digital Disruption Era - Kajonjatupon, Pramkamon (Arts of Management Journal, 2024)
The article aimed to study the marketing communication of entrepreneurs in the digital disruption era. Evolving technology has affected lives, including occupational and business operations, which require adaptation. This article studied entrepreneurial marketing communication in the era of digital disruption. Digital technology has forced entrepreneurs to find innovative ways to communicate with customers. Customer communication channels and building relationships between companies and consumers have been facilitated by digital technology. Digital disruption has altered entrepreneurial business methods and interactions. Print media is being replaced by digitally presented content, obliging entrepreneurs to adapt to technological changes to match the competition. Companies not using digital technology in their work processes may be hindered, as traditional marketing methods may be inadequate for communicating with target audiences. Therefore, many businesses have established digital channels to provide customer service and support changing consumer behavior. To differentiate themselves from market leaders and competitors, social tracking is also used to measure consumer opinions on social media in place of traditional surveys.